TTHE FULFILLMENT OF CHILDREN’S RIGHTS TO MAINTENANCE AFTER DIVORCE AT THE SIBUHUAN RELIGIOUS COURT - Junida Sari Hasibuan; Purmana Hidayah Harahap (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effectiveness of fulfilling children’s rights to maintenance after divorce at the Sibuhuan Religious Court by examining the legal foundations, the implementation of court decisions, and the obstacles in their enforcement. This research employs a qualitative juridical-empirical approach through the analysis of statutory regulations, legal literature, and relevant court practices. The findings indicate that although fathers’ obligations to provide child maintenance are clearly regulated under both Islamic law and Indonesian positive law, their implementation in practice remains inadequate. The main obstacles include low legal awareness among the parties, economic constraints, weak mechanisms for monitoring the execution of court decisions, and institutional limitations within the Religious Court in ensuring continuous compliance. This study emphasizes that the effectiveness of child protection cannot rely solely on judicial rulings but requires strengthening institutional mechanisms, optimizing the role of mediation, and increasing public legal awareness. Therefore, fulfilling child maintenance rights after divorce should be positioned as an integral part of realizing substantive justice and protecting the best interests of the child.